Pengaruh Influencer Endorsement Terhadap Niat Pembelian Konsumen Pada Pengguna Tiktok Shop di Kota Samarinda: Indonesia - Shabrina Hafidzatul Ain; Hudyah Astuti Sudirman; Istimaroh . (CV. ITTC INDONESIA, 2025)
This study examines the influence of influencer endorsement on consumer purchase intention among TikTok Shop users in Samarinda City. The research is motivated by the rising role of social media, particularly TikTok, as a digital marketplace that connects influencers with potential buyers. The study aims to determine the extent to which influencer endorsements affect consumer buying decisions. A quantitative method was employed, using a questionnaire distributed to 110 active TikTok Shop users in Samarinda. Data analysis was conducted through simple linear regression. The results show that influencer endorsement has a positive and significant effect on purchase intention. Key factors include consumer trust, emotional connection, and the attractiveness of the influencer. These findings highlight the strategic role of influencers in shaping consumer behavior and provide valuable insights for businesses aiming to enhance digital marketing efforts through social media collaborations, particularly in the context of local e-commerce.